The association between the adenoid microbiome and chronic otitis media with effusion in children differs according to age - Jo, Jae-Won; Kim, Sung Kyun; Byun, Jae Yong; Hong, Seok Min; Kim, Bong-Soo (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionChronic otitis media with effusion (COME) can adversely affect childhood development, and while the adenoid has been considered a reservoir for bacterial pathogens contributing to the pathogenesis of COME, the role of the adenoid microbiome in COME remains unclear. This study analyzed both the adenoid and gut microbiome in children with and without COME to identify their potential roles in the disease’s pathogenesis.MethodsAdenoid samples were collected during surgery for adenoid microbiome analysis, while fecal samples were collected for gut microbiome analysis. Microbiome was analyzed using whole metagenome sequencing and subsequent bioinformatic analysis.ResultsA significant association between the adenoid microbiome and COME was detected, while no such association observed for the gut microbiome. The adenoid microbiome varied by age in the control group, but this age-dependent variation was perturbed in the COME group. Notably, in children aged 6–12 years, the adenoid microbiome was significantly associated with COME based on the type of middle ear fluid, where Streptococcus pneumoniae and Haemophilus influenzae were prominent indicators in the mucoid form of COME. The proliferation of these species in mucoid COME group was correlated with indicators for the serous COME group. The altered microbiome in COME patients may influence immune responses through the synthesis of spermidine and acetate, contributing to disease development.DiscussionThis study highlights the age-dependent contribution of the adenoid microbiome–particularly in children aged 6 to 12 years–to the pathogenesis of COME.